Pengukuran Kinerja Dengan Balanced Scorecard - Mariza, Ita (Journal the Winners: Economics, Business, Management, and Information System Journal, 2003)
Performance of the company influenced by two factors, internal factors (controllable factors) and external factors (uncontrollable factors). From the internal factors itself consist of two parts, from managerial skills and financial side. The external factors are politic condition, economics condition, culture, social, etc. To survive in the market the company have to have the competitive advantage, it can be mangerial skills or financial side. So, to improve our ability or advantage or strength, we have to know first the performance of the current condition. There are four perspective in the Balanced scorecard to measure the performance, financial perspective, customers perspective, internal business, and learning and growth. In this article, will be discuss about the controllable factors only and with Balanced scorecard to measure the performance of the company.